Open versus robotic-assisted partial nephrectomy in patients with intermediate/high-complexity kidney tumours: final results of the randomised, controlled, open-label, multicentre trial OpeRa - Grimm, Marc-Oliver; Bedke, J.; Nyarangi-Dix, Joanne; Khoder, W.; Foller, S.; Sommerfeld, H. -J.; Giessing, M.; Heck, M.; Meißner, W.; Slee, A.; Leucht, K.; von Rundstedt, F.; et al. (Annals of oncology, 2025)
Background - The prospective, randomised, open-label, multicentre OpeRa trial (NCT03849820) aimed to determine whether robotic-assisted partial nephrectomy (RAPN) is superior to open partial nephrectomy (OPN) in reducing 30-day post-operative complications during the treatment of intermediate/high-complexity renal tumours. - Patients and methods - Eligible patients aged ≥18 years had a renal tumour suitable for OPN or RAPN, a RENAL score ≥7, and an estimated glomerular filtration rate ≥50 ml/min/1.73 m2. Patients were randomised from 15 March 2019 to 23 November 2021 in 12 German hospitals and assigned (1 : 1) to undergo RAPN or OPN. Primary endpoint was the 30-day post-operative complication rate [Clavien-Dindo (CD) I-V] in the modified intention-to-treat population. We aimed to recruit 606 patients to detect ≥10% reduction in the primary endpoint for RAPN versus OPN. - Results - A total of 240 patients were randomised to RAPN (n = 123) or OPN (n = 117). Enrolment was stopped prematurely due to slow recruitment. After patient withdrawal post-randomisation, 117 patients underwent RAPN and 90 OPN. The primary endpoint was assessable in 112 and 89 patients, respectively. The 30-day complication rate did not differ between groups: RAPN 41/112 (37%) versus OPN 41/89 (46%) (one-sided: P = 0.088). The difference of −9.5% (95% confidence interval −23.1% to 4.2%) numerically favoured RAPN. The most frequent high-grade complications (CD III-IV) to post-operative day 30 (POD30) were urine leakage [RAPN 4/112 (4%) versus OPN 2/89 (2%)] and post-operative bleeding [2/117 (2%) versus 1/89 (1%)]. Compared with OPN, RAPN patients had longer operative and warm ischaemia times, shorter hospital stay, and reported better recovery, less opioid use, less pain, and improved quality of life (QoL) up to POD30. - Conclusions - There was no statistically significant difference in the 30-day complication rate between RAPN and OPN in this underpowered trial. Few high-grade complications occurred over the whole cohort with intermediate/high-complexity tumours. Despite less intense pain management, patients undergoing RAPN reported less pain and better QoL up to POD30.